Expression and Characterization of Recombinant β-1,3-Glucanase of Burkholderia cepacia (BiogenCC E76) Expressed in Escherichia coli Expression Systems - Tri Puji Priyatno; Fitriani Winangsih; Ifa Manzila; Maria Bintang (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2019)
Burkholderia cepacia (Bcc) BiogenCC E76 isolate is an endophytic bacterium producing cell wall degrading enzyme, glucanase, and antagonistic to fungal pathogens, such as Magnaporte grisea and Colletotrichum gloeosporioides. The glucanase is able to lyse fungal cell walls composed of glucan causing disintegrity of mycelia and fungi fail to infect plants. The purpose of this study was to clone, express, and characterize 48 kDa subunit of β-1,3-glucanase from Bcc isolate BiogenCC E76 using the Escherichia coli expression system. The 1,300 bp of the β-1,3-glucanase gene was constructed using the pET-32b vector in BamHI-HindIII restriction sites to generate the pET-Glu plasmid. The gene was fused with nucleotides sequence encoding Trx-tag, His-tag, and S-tag producing 65 kDa of recombinant β-1,3-glucanase. Gene expression in the construct was controlled by the T7 promoter and Trx-tag start codon through IPTG induction. The recombinant β-1,3-glucanase was then purified and its activities were tested at different pH and temperature conditions. Results showed that E. coli carrying pET-Glu overexpressed a 65 kDa protein in induced culture as a soluble protein that was expressed in periplasm. Purification result of the crude extract of the recombinant protein obtained 27% pure enzymes with a specific activity of 1,207.976 U/mg and purity level of 3.9 fold. This recombinant glucanase demonstrated optimal activity at 40°C and pH 5–7. A deeper study is needed to understand the role of 48 kDa subunit of β-1,3-glucanase has in antagonistic mechanism of Bcc against pathogenic fungi.